(untitled) (Research, Society and Development, 2022)
The main objective of this article was to carry out a behavioral analysis of the character Arthur Fleck played by Joaquin Phoenix from the movie Joker (Joker – Brazil), categorized as a drama, released in 2019, under the direction of Tood Philips and distributed by Warner Bros. In order to carry out this research, a total of fifteen scenes from the film were selected and, through them, the problem behaviors of the character were identified. Possible diagnostic hypotheses were raised, based on the diagnostic criteria of the DSM-V, and a functional analysis was carried out based on the behavioral-analytic theory. Through the results obtained, it was possible to identify that the behaviors presented by the character are side effects of a long history of punishment, shown throughout the plot. For the behavior analyst, behavior is multidetermined, that is, a product of phylogenesis, ontogenesis and culture. Analysts will act on ontogenesis, performing a functional analysis. The diagnostic criteria described in the DSM-V tell us what is normal and what is not, so for the Behavior Analysis it is not predominantly taken into account in their analyses. Punishment and other forms of coercion were introduced into society’s culture as routine actions and their side effects can most often generate aggression, avoidance behavior and avoidance behavior.